The revolution of 1861 : the American Civil War in the age of nationalist conflict - Fleche, Andre M. (Civil War America (Series), 2012)
Grounding the causes and philosophies of the Civil War in an international context, Fleche examines how questions of national self-determination, race, class, and labour the world over influenced American interpretations of the strains on the Union and the growing differences between North and South.